Immunohistochemical expression of E-cadherin and CD44 adhesion molecules in oral squamous cell carcinoma - Asmaa S Al janabi; Seta A Sarkis (College of Dentistry/ University of Baghdad, 2014)
Background: Head and neck squamous cell carcinoma is the sixth most common cancer world wide. Despite greater emphasis on multi-modality therapy including surgery, radiation and chemotherapy, advanced stage head and neck squamous cell carcinoma continues to have poor 5-year survival rates (0-40%) that have not significantly improved in the last (30) years. To improve outcomes for this deadly disease , It is required a better understanding of the mechanisms underlying head and neck squamous cell carcinoma tumor growth, metastasis, and treatment resistance. This study evaluates the Immunohistochemical expression of E-cadherin and CD44 adhesion molecules in OSCC and to correlate the expression of either marker with each other, with lymph node metastasis and with tumor grade. Materials and methods: Thirty blocks of OSCC were included in this study. An immunohistochemical staining was performed using anti E-cadherinand anti CD44 monoclonal antibodies. Results: Negative immunohistochemical expression of E-cadherin was found in(66.7%)of the cases and only (33.3%)revealed positive immunoexpression. Positive CD44 immunoreaction was seen in(86.7%)of the cases. There was no statistically significant correlation regarding either marker with respect to the tumor stage, grade and lymph node matastasis. Moreover anon-significant correlation was found between the expression of both markers. Conclusions: this study revealed negative E-cadherin expression in two thirds of the cases, while positive CD44 was illustrated in most of them. Non- significant correlation was found regarding the expression of both markers with tumor stage, grade and lymph node status. Inverse significant correlation was found regarding CD44 expression with the clinical presentation of the study sample. In addition, non significant correlation was found between the E-cadherin and CD44 immunoexpression.